FRAGMENTATION OF FOAMED SILICIC MELTS: AN EXPERIMENTAL STUDY - Martel C.; Dingwell D.B.; Spieler O.; Pichavant M.; Wilke M. (My University, 2000)
We present the first experimental investigation of the fragmentation behavior of two-phase (melt+gas) rhyolitic systems under rapid decompression. Two-phase samples have been generated by foaming water-oversaturated rhyolitic melts up to 900°C and up to 18 MPa prior to rapid decompression in a fragmentation bomb. The fragmented particles or experimental pyroclasts were recovered for analysis. Several features of naturally foamed pumices have been reproduced, including the generation of both isotropic and tube pumices. We focus here on the fragmentation behavior. Fragmentation occurred through a layer-by-layer process, in the brittle regime of melt response. We investigated the influence of the magnitude of the decompression (4 to 18 MPa), the porosity (0 to 85 vol%) and the pore morphology (tube versus isotropic) on the fragment size distribution. Less vesicular samples (porosity50 vol%) yield coarser fragments when decompressed below 15 MPa and finer fragments when decompressed above 15 MPa. Increasing decompression of the vesicular samples results in a decrease in fragment size of 0.2 Φ unit/MPa. The presence of tubes instead of isotropic pores in vesicular samples generates finer fragments under decompression. Implications for dome eruptions are discussed.